Sustainable reverse logistics optimization with triple bottom line approach: An integration of disassembly line balancing - Budak, Ayşenur (Elsevier Sci Ltd, 2020)
The objective of this study is to develop the sustainable reverse logistics network with integration of disassembly line balancing to examine decisions in view of Triple Bottom Line. The Triple Bottom Line approach is a framework that considers three strategies which are economic, environmental, and social. Disassembly has great importance in reverse logistics operations. Therefore, disassembly line balancing approach has been integrated into sustainable reverse logistics network problem for the first time. A Multi period Multi-Objective Mixed Integer Nonlinear Programming model is proposed and solved with Improved Augmented Epsilon Constraint (AUGMECON-2) technique. Pareto optimal solution set is obtained. In order to demonstrate the applicability of the suggested model, developed solution procedure has been applied on end of life mobile phone recycling network. Objectives are indicated as social impact maximization, economic and environmental effect minimization. This study is applied for a three-year time period. Disassembly processes are also taken into account. The model respectively determines: (i) optimal quantity of WEEE between the facilities and inventory amounts, (ii) the number of workstations in disassembly centers (iii) the number of facilities that will be opened (iv) optimal task assignments to workstations in disassembly centers. Sensitivity analysis is proposed to examine the impact of incremental changes in WEEE amounts on the sustainable reverse logistics network. According to each scenario the number of changes in facilities, objective function values and tasks assigned to workstations are specified. This developed model could offer managers to take strategic decisions in recycling processes with regard to environmental and social impact and help to gain managerial insights as well. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Sustainable reverse logistics; Mixed integer nonlinear programming; Multi objective optimization; Triple bottom line; Disassembly line balancing